2007
DOI: 10.1080/15216540701335724
|View full text |Cite
|
Sign up to set email alerts
|

The tammar wallaby: A model to examine endocrine and local control of lactation

Abstract: SummaryMarsupials, such as the tammar wallaby (Macropus eugenii), have adopted a reproductive strategy that is very different to eutherians. Both the rate of production and the composition of milk changes progressively during the lactation cycle to meet the nutritional demands of an altricial young. The tammar therefore provides a valuable model to study changes in milk composition, and in particular the genes that code for proteins secreted in the milk, to more accurately assess the role of gene products regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In addition to acting independently to produce milk of different composition, the two adjacent mammary glands involute at different times. This further supports the concept that mammary function is regulated by local factors, most likely by milk proteins that act through an autocrine mechanism [53].…”
Section: Discussionsupporting
confidence: 81%
“…In addition to acting independently to produce milk of different composition, the two adjacent mammary glands involute at different times. This further supports the concept that mammary function is regulated by local factors, most likely by milk proteins that act through an autocrine mechanism [53].…”
Section: Discussionsupporting
confidence: 81%
“…Pathways deregulated in ΔMat neonates mostly relate, but are not restricted, to aspects of lipid metabolism that are crucially engaged when a suckling‐based, lipid‐rich diet is initiated. In marsupials, milk composition changes gradually during the course of lactation (Brennan et al , ). This is in striking opposition to eutherians, which have to adapt to an abrupt transition in energy substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Marsupial milk provides essential nutrients and putative growth factors for the development of the young, and cross-fostering experiments have shown that milk controls postnatal development (4,95). Endocrine and other factors, potentially intrinsic to the mammary gland, are likely to control milk secretion (36), and marsupial milk contains autocrine/paracrine regulators of the mammary gland (11,67). In special circumstances, macropod marsupials (kangaroos and wallabies) such as the tammar wallaby (Macropus eugenii) and red kangaroo (Macropus rufus) may present ACL, feeding two young of different ages concurrently with milk of different compositions from adjacent mammary glands, a newborn pouch young and one a few months older (51,68).…”
Section: Marsupial Lactation: Mammary Gland Sequencing Of the Marsupimentioning
confidence: 98%